Dinamika Epidemiologi Demam Berdarah Dengue dalam Perspektif Kesehatan Masyarakat: Tren Satu Dekade dan Variabilitas Iklim di Nusa Tenggara Barat - Eva Hikmatul Damayanti; Nurhidayati Nurhidayati; Deasy Irawati; Marisa Syavitri (Malahayati Nursing Journal, 2026)
ABSTRACT Dengue hemorrhagic fever remains a pressing public health concern in tropical regions, although the influence of climatic factors varies across local settings. This study aims to describe the epidemiological patterns of dengue over a ten-year period in West Nusa Tenggara (NTB), Indonesia, and to examine its association with climate variability. Secondary annual data from 2015 to 2024 were analyzed, including dengue incidence, mortality, and case fatality rate (CFR), along with meteorological indicators such as average and maximum temperature, relative humidity, rainfall, number of rainy days, and duration of sunshine. Descriptive statistics were performed, followed by simple linear regression to explore potential relationships. Time series modeling was applied to assess predictive capacity. Dengue incidence ranged from 10.7 to 88.9 per 100,000 population (mean 51.7/100,000), with CFR consistently below 2%. Annual variations coincided with major disruptive events, including the 2018 earthquake and the COVID-19 pandemic. Linear regression analysis demonstrated consistent patterns: relative humidity showed a positive association with incidence (B ≈ +9.8, R² up to 0.45, p = 0.071 when pandemic years were excluded), whereas average temperature and sunshine duration exhibited inverse relationships. Rainfall and number of rainy days showed weak and inconsistent associations. Time series analysis using Holt’s exponential smoothing captured short-term variability (stationary R² = 0.82) but produced relatively high prediction error (MAPE 44%). In NTB, dengue incidence fluctuates annually and is influenced by climatic variability as well as extraordinary events such as earthquakes and the COVID-19 pandemic. Relative humidity appears to be the most consistent climatic determinant. Time series modeling reflects short-term trends but lacks precision, underscoring the importance of strengthening local surveillance systems. Keywords: Dengue Hemorrhagic Fever, Climate Variability, Epidemiology, Humidity, West Nusa Tenggara.  ABSTRAK Demam berdarah dengue masih menjadi masalah kesehatan masyarakat yang mendesak di wilayah tropis, namun pengaruh iklim bervariasi antar konteks lokal. Penelitian ini bertujuan untuk menggambarkan epidemiologi demam berdarah dengue selama satu dekade di Nusa Tenggara Barat (NTB), Indonesia, dan mengkaji hubungannya dengan variabilitas iklim. Data tahunan sekunder dari tahun 2015–2024 dianalisis, meliputi insiden demam berdarah, mortalitas, dan tingkat fatalitas kasus (CFR) beserta indikator meteorologi (suhu rata-rata dan maksimum, kelembapan relatif, curah hujan, hari hujan, dan durasi sinar matahari). Statistik deskriptif dilakukan, dilanjutkan dengan regresi linier sederhana untuk mengeksplorasi hubungan. Pemodelan deret waktu diterapkan untuk menilai potensi prediktif. Insiden dengue berkisar antara 10,7 dan 88,9 per 100.000 penduduk (rata-rata 51,7/100.000), dengan CFR secara konsisten di bawah 2%. Fluktuasi tahunan bertepatan dengan peristiwa anomali seperti gempa bumi tahun 2018 dan pandemi COVID-19. Regresi linier menunjukkan tren yang konsisten: kelembapan relatif berkorelasi positif dengan insiden (B ≈ +9,8, R² hingga 0,45, p = 0,071 ketika tahun pandemi tidak termasuk), sementara suhu rata-rata dan durasi sinar matahari berkorelasi terbalik. Curah hujan dan hari hujan memberikan kontribusi asosiasi yang lemah dan tidak konsisten. Analisis deret waktu (pemulusan eksponensial Holt) menangkap variabilitas jangka pendek (R² stasioner = 0,82) tetapi menunjukkan kesalahan prediksi yang tinggi (MAPE 44%). Di NTB, insiden demam berdarah berfluktuasi setiap tahun, dipengaruhi oleh variasi iklim serta kejadian luar biasa seperti gempa bumi dan wabah COVID-19. Kelembapan menunjukkan hubungan paling konsisten dengan insiden. Pemodelan deret waktu mencerminkan pola jangka pendek tetapi kurang presisi, sehingga menyoroti pentingnya sistem pengawasan lokal. Kata Kunci: Demam Berdarah, Perubahan Iklim, Epidemiologi, Kelembaban, Nusa Barat Tenggara.